UMKM sebagai Aktor Komunikasi dalam Mendukung Pemberdayaan Ekonomi di Kawasan Destinasi Wisata Masjid Cheng Hoo dan Jati Sewu - Eka Wahyu Muria Ningsih; Adelia Aini Intan; Mohammad Insan Romadhan (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study examines the contribution of Micro, Small, and Medium Enterprises (MSMEs) actors in supporting community economic empowerment through their strategic role in strengthening tourist attractions in two destinations in East Java, namely religious tourism of Cheng Hoo Mosque Pasuruan and natural educational tourism of Jati Sewu Gresik. This research is based on the reality of tourist destinations that are the target of the study, where the role of MSMEs in both areas reflects a significant role in strengthening tourist attractions in destinations for visitors. Cheng Hoo Mosque Pasuruan and Jati Sewu Gresik have become new growing spaces for MSMEs that not only sell food, drinks, or tourist services, but also convey the distinctive values of the destination to visitors through direct interaction and the products sold. The method used is descriptive qualitative with a content analysis approach. The data collected was obtained from participatory observations in the field directly with MSME actors, and supported by secondary data obtained from various online sources such as news articles, tourism websites, and official information from the two related destinations. The results show that MSMEs in these two tourist destinations not only play a role in enriching the variety of attractions offered to tourists, but also play an important role in supporting the economy of the surrounding community. Trade activities carried out by MSME players around the tourist area directly create new economic opportunities while increasing community participation in tourism dynamics. In addition, MSMEs also create a more authentic, communicative, and inclusive travel experience for tourists.